Policy Inconsistency and External Debt Service. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
In this paper it is argued that the willingness of debtors to make external debt-service payments reflects, in part, their inability to credibly and permanently suspend debt service. The benefits of a credible debt-service suspension would include increased private investment. But this would, in turn, tend to create conditions in which it would then be optimal for the government to resume payments. Thus, debt remains a threat even after the announcement of suspension of debt service. It follows that the expected benefits of such a suspension are limited and may be offset by penalties imposed by creditors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Investment Equilibrium; Investment; Tax Rate; WP